Dalitz plot analysis of [eta] c → K+K- [eta] and [eta] c → K+K-π0 in two-photon interactions - Lees, Jean-Pierre; Adametz, Aleksandra; Uwer, Ulrich (Physical review. D, Particles, fields, gravitation, and cosmology, 2014)
We study the processes γγ→K+K−η and γγ→K+K−π0 using a data sample of 519 fb−1 recorded with the BABAR detector operating at the SLAC PEP-II asymmetric-energy e+e− collider at center-of-mass energies at and near the Υ(nS) (n=2,3,4) resonances. We observe ηc→K+K−π0 and ηc→K+K−η decays, measure their relative branching fraction, and perform a Dalitz plot analysis for each decay. We observe the K∗0(1430)→Kη decay and measure its branching fraction relative to the Kπ decay mode to be R(K∗0(1430))=B(K∗0(1430)→Kη)B(K∗0(1430)→Kπ)=0.092±0.025+0.010−0.025. The ηc→K+K−η and K∗0(1430)→Kη results correspond to the first observations of these channels. The data also show evidence for ηc(2S)→K+K−π0 and first evidence for ηc(2S)→K+K−η.
Im Titel ist "eta" als griechischer Buchstabe dargestellt
Im Titel sind "+", "-" in K+K- und "0" in π0 hochgestellt und "c" in eta c tiefgestellt
Gesehen am 11.08.2020